Physics and Modelling of Wind Erosion - Shao, Yaping (Springer, 2017)
This book provides a comprehensive summary of the recent developments in wind erosion research and a clear outline of its future directions. The physics of wind erosion, from particle entrainment to transport and deposition, is described with rigor from the viewpoints of fluid dynamics and soil physics. The techniques for quantitative wind- erosion prediction through computational modelling constitutes a unique feature of this book in contrast to others published in the same field. The author has advocated the development of integrated wind-erosion modelling systems which couple dynamic models for the atmosphere and land surface with spatially distributed data for land-surface conditions (...)